Chameleon TFE3-translocation RCC and How Gene Partners Can Change Morphology: Accurate Diagnosis Using Contemporary Modalities. (18th May 2022) - Tretiakova, Maria S.
Abstract : Translocation renal cell carcinoma (tRCC) with TFE3 gene rearrangements has been born as a distinct entity 20 years ago. These relatively rare tumors were notable among other RCC subtypes because of their disproportionally high incidence among children and young adults. Initial reports were focused on describing unifying morphologic criteria and typical clinical presentation. Follow-up studies of ancillary immunohistochemical and hybridization techniques provided additional diagnostic tools allowing recognition of tRCC tumors in practice. However, a growing body of literature also expanded the clinicomorphologic spectrum of tRCCs, to include a significant morphologic overlap with other RCC variants thus blurring the diagnostic clarity of this entity. More recent molecular studies utilizing next-generation sequencing technology accelerated recognition of numerous novel gene partners fusing at different breakpoints with the TFE3 gene. Accumulating data indicates that morphologic and clinical heterogeneity of tRCC could be explained by fusion subtypes, and knowledge of TFE3 partnering genes may be important in predicting tumor behavior. Herein we provided a comprehensive analysis of ∼400 tRCC cases with known TFE3 fusion partners, estimated their relative incidence and summarized clinicomorphologic features associated with most common fusion subtypes. Our data was based on an extensive literature review and had a special focus on comparing immunohistochemistry, fluorescent in situ hybridization and contemporary molecular studies for the accurate diagnosis of tRCC.